Investment Feasibility Evaluation Analysis in Beverage Partnership Business: Case Study on Fore Coffee in Mataram City - Anggun Cantika; Alamsyah AB (LP2M IAIN Palopo, 2026)
The rapid growth of Indonesia's modern coffee industry through franchise partnerships offers significant investment opportunities but also financial risks. This study analyzes the investment feasibility of Fore Coffee's partnership business in Mataram City using financial indicators. Using a mixed-methods case study approach, the study targeted stakeholders of one Fore Coffee outlet, including managers, employees, and consumers. Data collection through interviews, observations, documentation, and questionnaires was analyzed using NPV, IRR, PP, PI, and sensitivity analysis. The results show an NPV of IDR 3,250,214,444, an IRR of 58.9% (exceeding the cost of capital by 10%), PP of 1 year and 11 months, and PI of 2.85, confirming the investment feasibility. The sensitivity analysis proves the project's resilience to a 10% decline in revenue. It is concluded that the Fore Coffee partnership investment in Mataram is highly financially feasible, serving as a reference for potential investors in decision-making.